The competitiveness of turkish agriculture in the context of European economic integration - Tekçe, İ. Mahmut (My University, 2006)
Avrupa Birliği ile yürütülen müzakereler çerçevesinde, Türkiye ekonomisinin en problemli sektörlerinden biri tarım olacaktır. Türk tarımı pek çok açıdan Avrupa Birliği tarımından farklıdır ve Türk tarımının Avrupa Ortak Tarım Politikası’na uyumunun zor olacağına kuşku yoktur. Ancak Türk tarımında gerçekleşecek bir dönüşüm, uzun süredir ihmal edilen sektörün kaderini değiştirebilir. Dolayısıyla tarım sektörünün rekabetçiliği, Türkiye’nin yakın gelecekte karşılaşacağı en önemli siyasi ve ekonomik konu olacaktır. Rekabetçiliği geliştirmeye yönelik politikalar hem üretim ve ihracatı artıracak, hem de kırsal alanların gelişmesini sağlayacaktır. Bu çalışma, 1980’den günümüze Türk tarım ürünlerinin rekabetçiliğini incelemekte ve hem müzakereler sürecinde hem de gelecekteki tam üyelikte Türkiye’nin tarımında rekabetçiliği artırması için uygulaması gereken politikaları tartışmaktadır. Ayrıca bu çalışmada Balassa rekabetçilik endeksi, gelişmekte olan ülkelerdeki tarım sektörlerini daha iyi açıklayacak şekilde yeniden formüle edilmektedir.

In the process of accession negotiations with the European Union, one of the most problematic sectors of Turkish economy will be agriculture. Turkish agriculture is different from the European agriculture in many ways, and there is no doubt that the harmonization of Turkish agriculture to the Common Agricultural Policy of the EU will not be easy. But, such a transformation in the Turkish agriculture could change the destiny of the sector that has been neglected for a long time. In this context, the competitiveness of agriculture is one of the major political and economic challenges for the near future of Turkey. Policies targeted at improving competitiveness would affect not only production or export levels, but would also implicate the development of rural regions. This study aims to explore the competitiveness of Turkish agricultural products since 1980, and tries to determine the proper agricultural and rural policies for Turkey in order to enhance its competitiveness in the process of negotiations, and eventually in the time of full membership. This study also aims to reformulate the Balassa competitiveness index in such a way to explain the changing patterns of agricultural sectors in the developing countries.
Keywords: Rekabet_Türkiye; Tarım_Avrupa Birliği; Tarım_Türkiye